HUBUNGAN PERILAKU PENGGUNAAN KELAMBU BERINSEKTISIDA DENGAN KEJADIAN MALARIA DI DESA RINDI WILAYAH KERJA PUSKESMAS TANARAING KABUPATEN SUMBA TIMUR - Anastasia Tiyas Walidiyati (Universitas Citra Bangsa, 2019)
Malaria is a contagious disease that is very dominant in the tropics and subtropics and can cause the death of more than millions of people each year. Nationally, NTT Province is the third highest province of malaria morbidity after Papua and West Papua. Various efforts have been made by the government to reduce morbidity and mortality due to malaria, one of which is distribution of indexed bed nets, but malaria morbidity rates are still quite high. The purpose of this study was to identify the relationship between the behavior behavior of insecticide-treated bed nets and the incidence of malaria in the village of Rindi in the Working Area of Tanaraing Health Center, East Sumba Regency. The design in this study is a correlational study with a cross sectional approach and the sampling used is probability sampling with a sample of 168 respondents. The results showed that 122 (73%) respondents behaved positively and 46 (37%) respondents behaved negatively about the use of insecticide-treated bed nets. The multivariate test results with logistic regression with the forward method obtained p value 0.002 <0.005 there is a relationship between the behavior of mosquito nets using malaria incidence with a probability level of 81% which means that someone who has negative knowledge, attitudes and behavior will suffer malaria as much as 81%. Efforts to eradicate and prevent malaria are not only done by the use of insecticidetreated bed nets but can be done by manipulating the environment, namely the use of wire mesh at home and the use of repellent. Health workers are expected to improve health promotion about malaria and make home visits. It is also hoped that local village officials will increase the use of resources owned by the village to support the malaria elimination program. Keywords : Malaria Incidence, Behavior, Insecticide-Treated Bed Nets.